The role of values in white-collar crime : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Bradshaw, Nicholas W (Massey University, 1998)
In this thesis I wish to respond to the claim that there is a need to elaborate a proper and useful relationship between sociology and art; that is, to find out what, if any, limitations there are to a sociological analysis of art. To a large degree, sociological approaches to literature have provided insights useful and similar to the present focus of artistic production. There are some who claim that sociology cannot replace or substitute art criticism, that the aesthetic merit of any work is beyond the scope of sociological analysis. This is a position which I consider to be flawed. Even those who correctly criticise the reductionist tendencies of some sociological approaches nevertheless do not properly acknowledge the changing nature of what is considered to be of aesthetic quality. To ask the question 'What is art?' is, in fact, to ask about that which is considered to be art by society, or – more correctly – by certain of its key members. Consequently, a range of definitions of art and related practices are excluded. In this thesis, I focus on women's experience, in the light of the evidence of the way in which women's art has traditionally been ignored or devalued. The origins of aesthetics as a distinct discipline (the study of the nature of art) are seen to be linked to other social and historical developments; that is, the prior and accompanying constitution of art itself as a self-contained discourse and practice. Feminists, in particular, whose focus involves a concern with cultural production, have pointed to the way in which art is socially-constructed. They have sought to address the way in which the dominant discourse about art has contributed to the disadvantages and inferior position experienced by women in the arts and, indeed, to the wider societal oppression of women. Through the arts, male-defined representations of the world are valued, and the very notion of 'artist', as it has been commonly held, has reinforced women's secondary status. A socialist-feminist critique is outlined, in terms of its challenge to conventional art-critical practices. It recognises the constraints imposed on women by art critics in their gatekeeping capacity. The role of the state in the patronage of the arts is seen as another example of the political nature of cultural production, and the discourse within which the state's role is defined and practised is seen to be a political and ideological exercise. A socialist-feminist approach requires the validation of women's realities, in particular, and a general rejection of representations that distort or mystify social relations in the interests of hegemonic ideologies. In addition to the critique of the content of images, it seeks to transform the structural elements of cultural production. To generate a specific prescription, of a conclusive and exhaustive nature, for a genuinely democratic form of art practice is inappropriate. Instead, for the requirements of an authentic socialist-feminist critique, the political nature of cultural production and the changing conjunctural aspects of cultural production are to be fully acknowledged and incorporated.
Keywords: White collar worker psychology; White collar crimes, New Zealand